Entoloma sicoense, a new species in the subgenus Cyanula (Entolomataceae) - Fachada, Vasco; Pedreiro, Helder; Raimundo, Susete; Noordeloos, Machiel; Dima, Bálint; Marques, Guilhermina (Phytotaxa, 2023)
Entoloma sicoense, a bluish gray mushroom species belonging to section Poliopodes, is described as a new addition to the subgenus Cyanula. This study presents the phylogeny, taxonomy, and ecological significance of Entoloma sicoense, which inhabits mossy broad-leaved forests in the eastern North Atlantic region. The discovery of this new species expands our understanding of fungal diversity and highlights the ecological significance of the subgenus Cyanula in Serra de Sicó. Entoloma sicoense exhibits specific morphological characteristics, such as slate gray basidiomata, a smooth concolorous stipe, and a sterile gill edge rich in brilliant granules. This research underscores the importance of documenting and describing new species in Serra de Sico´ for comprehensive cataloging, conservation efforts, and further exploration of its ecological role within the local ecosystem. The new species is presented with morphological, illustrated description as well as molecular work and comparison with similar species.